Superheated Steam Technology-Assisted Pasteurization For Milk: Nutritional Composition And Heavy Metal Contaminant Analysis - Baharuddin, Muhammad Zharfan Ahmad (Universiti Sains Malaysia, 2021)
The heat treatment process of raw milk is important in eliminating or inactivating pathogenic and spoilage organisms present to ensure the processed milk is safe for consumption and further extend the shelf life of milk. Superheated steam-assisted pasteurization is considered as a possible alternative to conventional pasteurization method due to low energy consumption and the effectiveness in the inactivation of microbial activity in food. In this extended literature study, the effects of superheated steam-assisted pasteurization of milk on its nutritional composition and heavy metal contaminant level was investigated. It is found that there are yet no evidence of the intended objectives of this study due to a lack of research in this area. However, superheated steam-assisted pasteurization process is possible to replace the current conventional pasteurization method in the industry if more research is done in the future to investigate the effects of this process on milk’s nutritional composition and its heavy metal contaminant levels.